Determination of total phenolic content, membrane stabilizing and thrombolytic activities of crataeva nurvala bark extract - Sahena, Ferdosh; A. K., Azad; Z.K., Labu; Sarker, Md. Zaidul Islam (2018)
Crataeva nurvala (C. nurvala) is a medicinally active plant, potentially used as traditional means of treating many health ailments such as prostatitis, prostate enlargement, inflammatory conditions, cardio-protective, thyroid and endocrine disorder and urinary tract infection respectively in the rural region of Tangail, Jamalpur, Sherpur and Barishal district since primitive era.